Electrochemical properties of Robson type macrocyclic dicopper(II) complexes - Alegria, Elisabete (2018)
The redox properties of the 1,10-phenanthroline containing Robson type symmetrical macrocyclic dicopper(II) complex [Cu2L(H2O.phen)2](ClO4)2 1 (L = μ-11,23-dimethyl-3,7,15,19-tetraazatricyclo-[19.3.1.18 19,13,21] he p t a c o s a-1(24) , 2, 7, 9, 11, 13(26), 14, 19, 21(25), 22-decaene-25,26-diolate) and of its dicopper(II) precursor [Cu2L(H2O)2](ClO4)2 2 have been investigated by cyclic voltammetry and controlled potential electrolysis in different organic solvents. They exhibit two consecutive reversible one-electron reductions assigned to the CuIICuII ® CuICuII ® CuICuI cathodic processes. The results suggest that, in solution, phenanthroline does not coordinate to the metal in complex 1, but its H-bonding interaction with the water ligands can be preserved.